The Usage: A Historical Analytical Study - Bleik, Rana Aniss (Journal of Arabic Language Sciences and Literature, 2023)
This study aims to shed light on the development of the speech of Arabs from the era of ignorance until our age and exposing its beauties and effects in understanding the literary texts in general and the texts of the Hadiths specifically. This chapter being the most accurate in Rhetorics, has not been tackled by the researchers to expose its beauties and treasures. The reason is the rarity of the resources and references in it, and the excessive difficulties that stand an obstacle in the face of the researcher should one attempts to engage this deep ocean.It has been rare to find this type of Rhetoric in the poetry of the Arabs and their speeches from the century of ignorance until the Abbasid century despite the abundance of examples present in the Qur’an and the honorable prophetic sayings due to their lack of attention, most likely, to Figurative rhetorics. Thereafter the Umayyads and then the Abbasids came about and started attending to documenting the sciences, and the studies of rhetorics began and the scholars started compiling and editing, however, the usage of rhetorics was not found in one organized compilation and the poets have not paid attention to it and have rarely beautified their poems with it.In the seventh century during the era of the Mamelukes and due to the reversion of the poets to the science of Figurative rhetorics. and innovating in it, they used it abundantly in their poems. However, this did not last for long, and it dwindled.I have elucidated all of that in my study and have exposed the beauties of the implementation through the Qur’anic texts and the honorable prophetic sayings and the poetic manifestations showing its meanings and the beauty of implementation in it
Keywords: The usage (Istikhdam); Meanings; Beauties; Rhetorics; Applied Proofs